1991
DOI: 10.3109/01050399109070791
|View full text |Cite
|
Sign up to set email alerts
|

The Use and Benefit of In-the-ear Hearing AidsA four-year follow-up examination

Abstract: The present investigation was performed in order to evaluate the use and benefit of in-the-ear hearing aids (ITE-HAs) after a 4-year observation period, and to examine the validity of this type of hearing aid. A sample of 537 subjects still in possession of ITE-HAs, fitted in 1985, responded to a postal questionnaire in 1989, including questions identical to the first follow-up in 1985. The 537 persons correspond to 60% of the originally fitted sample of 894 subjects. The investigation indicated that no change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…In Brooks' sample, 80 those who were using a hearing aid at 1 year postfitting were all using their aids at 10 years after fitting. Henrichsen and colleagues 81 showed that there was no evidence of change in hearing aid use of and benefit from ITE aids between 6 months and 4 years, among those participants who continued using the same aid for 4 years; those who used their aids at 4 years used and benefited from them equally as much as at 6 months postfitting. Kyle and Wood, 66 in a sample of 25-55 year olds showed that those who were fitted for less than 2 years used their aids more (both at work and at home) than those who were fitted between 2 and 10 years earlier.…”
Section: Resultsmentioning
confidence: 99%
“…In Brooks' sample, 80 those who were using a hearing aid at 1 year postfitting were all using their aids at 10 years after fitting. Henrichsen and colleagues 81 showed that there was no evidence of change in hearing aid use of and benefit from ITE aids between 6 months and 4 years, among those participants who continued using the same aid for 4 years; those who used their aids at 4 years used and benefited from them equally as much as at 6 months postfitting. Kyle and Wood, 66 in a sample of 25-55 year olds showed that those who were fitted for less than 2 years used their aids more (both at work and at home) than those who were fitted between 2 and 10 years earlier.…”
Section: Resultsmentioning
confidence: 99%
“…This finding indicates that 'follow-up support' must be considered a key factor in the outcome of hearing-aid fitting in older people. Although the significance of 'followup support' has been emphasized in previous studies (Gianopoulos, Stephens, and Davis 2002;Henrichsen et al 1991;Hickson and Worrall 2003), its value, to date, has not been scientifically assessed or documented. The strength of the present study was the relationship between the statements about daily hearing-aid use and the participant's experience of 'follow-up support'.…”
Section: Follow-up Supportmentioning
confidence: 99%
“…The use of hearing aids has been associated with higher pre-fitting expectations and greater acceptance of hearing loss (Jerram and Purdy 2001). The need for and benefit of follow-up support, which has been defined as organized check-ups and accessibility to professionals, have been documented (Gianopoulos, Stephens, and Davis 2002;Henrichsen et al 1991;Hickson and Worrall 2003;Takahashi et al 2007), although not specifically for older adults. It has been argued that the medically and technically focused audiological follow-up support that is traditionally practiced should shift to a holistic approach that includes functional assessment, psychosocial aspects, communication skills and educating significant others (Falkenberg 2007).…”
Section: Introduction and Purposementioning
confidence: 99%
“…On the other hand, motivation and perception of the hearing impairment seem to be important predictors of successful rehabilitation .Use of hearing aids has been associated with higher pre-fitting expectations and greater acceptance of hearing loss (Jerram and Purdy 2001). The need and the benefit of follow-up support have been documented Henrichsen et al 1991;Takahashi et al 2007), though not specifically for older adults. It has been argued that the former medical and technical focused audiological follow-up support traditionally practiced, should be a holistic, multi-disciplinary approach including psychosocial aspects, communication skills and educating significant others.…”
Section: Introduction and Purposementioning
confidence: 99%